2006
DOI: 10.1098/rstb.2006.1814
|View full text |Cite
|
Sign up to set email alerts
|

Historical approaches to post-combat disorders

Abstract: Almost every major war in the last century involving western nations has seen combatants diagnosed with a form of post-combat disorder. Some took a psychological form (exhaustion, combat fatigue, combat stress reaction and post-traumatic stress disorder), while others were characterized by medically unexplained symptoms (soldier's heart, effort syndrome, shell shock, non-ulcer dyspepsia, effects of Agent Orange and Gulf War Syndrome). Although many of these disorders have common symptoms, the explanations atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 49 publications
1
33
0
5
Order By: Relevance
“…A cluster analysis of symptoms showed that there was no difference in the patterning of symptoms between the two groups and that three groups of symptoms had predominated consistently in war syndromes throughout the 20th century: debility cluster (n = 847); somatic cluster (n = 434) and neuropsychiatric cluster (n = 575). 8 Australian research into Gulf War Syndrome yielded similar results. Australian Gulf War veterans reported symptoms more frequently and more severely when compared with matched military personnel who did not deploy to this conflict.…”
Section: New Understanding Of War Syndromessupporting
confidence: 72%
“…A cluster analysis of symptoms showed that there was no difference in the patterning of symptoms between the two groups and that three groups of symptoms had predominated consistently in war syndromes throughout the 20th century: debility cluster (n = 847); somatic cluster (n = 434) and neuropsychiatric cluster (n = 575). 8 Australian research into Gulf War Syndrome yielded similar results. Australian Gulf War veterans reported symptoms more frequently and more severely when compared with matched military personnel who did not deploy to this conflict.…”
Section: New Understanding Of War Syndromessupporting
confidence: 72%
“…In addition to clinical and epidemiological research, the Gulf War Syndrome controversy has prompted medical historians to rediscover an extensive international literature on poorly understood war-related symptom syndromes (for a detailed discussion, see Jones 2006). Controversial syndromes have occurred during and after virtually every major war dating back at least as far as the Crimean War of the 1850s and the US Civil War (Hyams et al 1996;Jones et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The role of the military mental health practitioners who work in FMHTs is to provide clinical, educational, and advisory support to operational commanders. In discharging their clinical function, the FMHT makes use of "Forward Psychiatry," a term which refers to a set of treatment principles that were first articulated in 1916 (Jones, 2006). These principles are described using the acronym "PIE," which refers to treatment delivery being proximal to the combat zone, being delivered immediately to those that need it, and delivered with the expectation of occupational recovery.…”
Section: Long-term Military Work Outcomes In Soldiersmentioning
confidence: 99%